Restrukturisasi Pembiayaan Murabahah Bermasalah (Studi Pada Bni Syariah Cabang Kendari) - Kalsum, Ummi; Rahmi, Rahmi (Li Falah: Journal of Islamic Economics and Business, 2017)
This thesis research analyzes the process of restructuring on financing the problematic murābahahat PT. BNI Syariah Branch of Kendari. The results prove that the implementation of financingrestructuring murābahah in PT. BNI Syariah Kendari Branch through rescheduling (rescheduling),reconditioning (Return requirements) and restructuring (reordering). While theconstraints of restructuring implementation on Murabahah financing in PT. BNI Syariah KendariBranch is originated from the financing customer itself either from the absence of good customer'sintention to settle the troubled financing due to unwilling restructuring and unclear sources ofpayment after the restructuring. The bank overcomes these obstacles by taking precautions inanalyzing the financing customers, and considering third party installments and taking decisiveaction with the sale of the customer's collateral assets.